Comparative allelopathic potential of metabolites of two Alternanthera species against germination and seedling growth of rice - Mehmood,A. (2014)
A laboratory study was conducted to investigate the allelopathic effect of aqueous extracts of plant parts of Alternanthera philoxeroides and A. sessilis and soil incorporated residues on germination and seedling growth of rice (Oryza sativa). Aqueous extracts prepared from different plant parts of Alternanthera species delayed rice germination. Alternanthera philoxeroides and A. sessilis inhibited rice germination by 9-100% and 4-49%, respectively. Germination of rice seeds was reduced with increasing concentration of aqueous leaf extracts of both weed species. Early seedling growth (root and shoot lengths) and seedling vigor index were significantly reduced by 5% aqueous leaf extract compared with distilled water treated control. Germination, root and shoot lengths, root and shoot dry weights and seedling vigor index of rice were drastically reduced by 3 and 4% in residue infested soil compared with residue free soil. The inhibitory effect of A. philoxeroides in terms of germination and seedling growth of rice was greater than that of A. sessilis. Five percent aqueous leaf extract and 4% residue infested soil of A. philoxeroides caused complete failure of rice seed germination. Alternanthera philoxeroides contained water soluble phenolics, namely 4 hydroxy-3-methoxy benzoic acid (16.19 mg L-1) and m-coumaric acid (1.48 mg L-1), whereas Alternanthera sessilis was rich in chlorogenic acid (17.85 mg L-1), gallic acid (11.03 mg L-1) and vanillic acid (9.88 mg L-1). The study indicates that the allelopathic potential of Alternanthera species may play an important role in enhancing the invasiveness of these species and may suppress rice plants in the vicinity.